The role of intangible assets and liabilities in firm performance: empirical evidence - Ahmed, Abdifatah; Mohd Ghazali, Nazli Anum (Emerald Group Publishing Ltd., 2018)
Purpose - The purpose of this paper is primarily to explore the extent of intangible assets and liabilities of large Malaysian companies. The authors also examine whether intangible assets and liabilities of a firm have similar or contrasting roles in firm performance. Design/methodology/approach - Using a direct and straightforward measure of intangible assets and liabilities, the authors examine a large pool of data from large Malaysian companies over a six-year period spanning from 2008 to 2013. Findings - The longitudinal analyses show a significant number of the sample companies, between 34 and 59.33 percent, have a consistent pattern of intangible liabilities. The authors also find firms with intangible liabilities have significantly underperformed financially than a control group of firms. In addition, the authors find that intangible liabilities have significant negative impact on firm performance whereas intangible assets have a contrasting positive impact on firm performance. Research limitations/implications - One limitation of this study is that the authors have only used a single measure of intangible assets and liabilities. Albeit the measures used are straightforward and more objective, there could be other measures to capture intangibles. Practical implications - The research findings have several theoretical as well as policy implications. Theoretically, the authors extend the resource-based view to the intangible asset-liability mix, affirming the crucial role of intangible resources in financial performance whilst introducing the unfavorable role of intangible liabilities in corporate financial performance. In terms of policy implications, the research findings provide initial empirical input to emerging calls for broader perspectives of intangibles, beyond intangible assets to include intangible liabilities, and therefore belong to an emerging paradigm toward the nature of intangibles. Originality/value - This study documents a rare empirical account of the contrasting roles of intangible assets and liabilities in corporate financial performance. © 2018 Emerald Group Publishing Ltd. All rights reserved.